Relaxation of stress occurring in Cd-Ni diffusion zone with formation of intermetallic phase - Bogdanov, V.V.; Kononenko, V.G.; Volosyuk, M.A.; Volosyuk, A.V. (Functional Materials, 2017)
Relaxation of mechanical stress occurring in Cd-Ni diffusion zone was studied by metallographic methods. Brittle relaxation of tensile stress was revealed in Cd₂₁Ni₅ intermetallic phase growing in the diffusion zone. Evaluation of this stress made by the geometry of macroscopic cracks in the intermetallic phase showed values being by a factor 1.2 lower than stress values calculated by volume defect related with the intermetallic phase formation. As plastic deformation within the intermetallic phase is excluded, whereas brittle relaxation begins at the Cd₂₁Ni₅-Ni boundary, it was concluded that induced in Ni compressive stress relaxed by plastic deformation mechanism to the level of Ni elastic limit.